2011
DOI: 10.2174/1874192401105010076
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Thyroid Dysfunction on Lipid Profile

Abstract: Thyroid dysfunction has a great impact on lipids as well as a number of other cardiovascular risk factors. Hypothyroidism is relatively common and is associated with an unfavorable effect on lipids. Substitution therapy is beneficial for patients with overt hypothyroidism, improving lipid profile. However, whether subclinical hypothyroidism should be treated or not is a matter of debate. On the other hand, hyperthyroidism can be associated with acquired hypocholesterolemia or unexplained improvement of lipid p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

26
262
3
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(309 citation statements)
references
References 146 publications
(208 reference statements)
26
262
3
18
Order By: Relevance
“…Serum HDL-C in the present study was nonsignificantly lower in hypothyroid patients compared to the controls, which is in agreement with previous studies (38,39). However, this finding differs from other studies (41,42), which reported a significant increase in serum HDL-C levels in hypothyroid patients.…”
Section: Discussionsupporting
confidence: 94%
“…Serum HDL-C in the present study was nonsignificantly lower in hypothyroid patients compared to the controls, which is in agreement with previous studies (38,39). However, this finding differs from other studies (41,42), which reported a significant increase in serum HDL-C levels in hypothyroid patients.…”
Section: Discussionsupporting
confidence: 94%
“…Elevated prolactin may result from untreated hypothyroidism because hypothalamic thyrotropin‐releasing hormone, which is commonly elevated in hypothyroidism, stimulates both prolactin synthesis and release from the pituitary 29. Hypothyroidism is associated with hypertension and elevations in HDL cholesterol 30, 31. Nevertheless, this mechanism is speculative.…”
Section: Discussionmentioning
confidence: 99%
“…9 The difference could be explained by our larger sample size of 50 individuals whereby the study in Tamil Nadu had a sample size of 30. have also reported similarly higher TG levels, but TC and LDL-C were also reported to be higher in SCH as in our study. 2,5 Contrary to all what is being said, an amazing result was presented in National Health Examination Survey III, in which 215 subjects with diagnosed SCH and 8013 Euthyroid individuals were checked for fasting lipid profile. Strangely no difference was found in the lipid profile picture of SCH and Euthyroid individuals.…”
Section: Discussionmentioning
confidence: 92%
“…10,28 In overt hypothyroidism also AIP levels have not been studied, but conflicting results were seen in studies investigating the impact of overt hypothyroidism on LDL-C subfractions, particularly LDL. 5 Though a recent study conducted on newly diagnosed hypothyroid patients showed an association between hypothyroidism and elevated LDL, other studies could not conclusively prove such an association. 29,30,31 All these results reiterate the need for studies on the association of fasting Lipid levels with SCH.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation